Rabphilin involvement in filtration and molecular uptake in Drosophila nephrocytes suggests a similar role in human podocytes - Estela Selma-Soriano (Disease Models & Mechanisms, 2020)
Drosophila nephrocytes share functional, structural and molecular similarities with human podocytes. It is known that podocytes express the rabphilin 3A (RPH3A)-RAB3A complex, and its expression is altered in mouse and human proteinuric disease. Furthermore, we previously identified a polymorphism that suggested a role for RPH3A protein in the development of urinary albumin excretion. As endocytosis and vesicle trafficking are fundamental pathways for nephrocytes, the objective of this study was to assess the role of the RPH3A orthologue in Drosophila, Rabphilin (Rph), in the structure and function of nephrocytes. We confirmed that Rph is required for the correct function of the endocytic pathway in pericardial Drosophila nephrocytes. Knockdown of Rph reduced the expression of the cubilin and stick and stones genes, which encode proteins that are involved in protein uptake and filtration. We also found that reduced Rph expression resulted in a disappearance of the labyrinthine channel structure and a reduction in the number of endosomes, which ultimately leads to changes in the number and volume of nephrocytes. Finally, we demonstrated that the administration of retinoic acid to IR-Rph nephrocytes rescued some altered aspects, such as filtration and molecular uptake, as well as the maintenance of cell fate. According to our data, Rph is crucial for nephrocyte filtration and reabsorption, and it is required for the maintenance of the ultrastructure, integrity and differentiation of the nephrocyte.